Lipid Chaperones and Metabolic Inflammation - Masato Furuhashi; Shutaro Ishimura; Hideki Ota; Tetsuji Miura (International Journal of Inflammation)
Over the past decade, a large body of evidence has emerged demonstrating an integration of metabolic and immune response pathways. It is now clear that obesity and associated disorders such as insulin resistance and type 2 diabetes are associated with a metabolically driven, low-grade, chronic inflammatory state, referred to as “metaflammation.” Several inflammatory cytokines as well as lipids and metabolic stress pathways can activate metaflammation, which targets metabolically critical organs and tissues including adipocytes and macrophages to adversely affect systemic homeostasis. On the other hand, inside the cell, fatty acid-binding proteins (FABPs), a family of lipid chaperones, as well as endoplasmic reticulum (ER) stress, and reactive oxygen species derived from mitochondria play significant roles in promotion of metabolically triggered inflammation. Here, we discuss the molecular and cellular basis of the roles of FABPs, especially FABP4 and FABP5, in metaflammation and related diseases including obesity, diabetes, and atherosclerosis.